2017
DOI: 10.1007/s40429-017-0162-y
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Structural Characteristics in Problematic Video Game Playing

Abstract: Purpose of ReviewThere are many different factors involved in how and why people develop problems with video game playing. One such set of factors concerns the structural characteristics of video games (i.e., the structure, elements, and components of the video games themselves). Much of the research examining the structural characteristics of video games was initially based on research and theorizing from the gambling studies field. The present review briefly overviews the key papers in the field to date.Rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 64 publications
2
50
0
2
Order By: Relevance
“…The present study identified a control motive as driving adolescent social media that may be reinforced by FoMO, nomophobia and powerful emergent structural characteristics of SNS. Similarly to games, where the acquisition of artefacts or rewards reinforce the gamer into prolonging the gaming experience (Griffiths & Nuyens, 2017;King, Herd, & Delfabbro, 2018), SNSs exhibit a plethora of structural features that engage adolescents further in habitual behaviours (Griffiths, 2018;Turel & Osatuyi, 2018). SNS intensity and network size have been found as significant predictors of mobile SNS applications which are associated with smartphone addiction (Salehan & Negahban, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The present study identified a control motive as driving adolescent social media that may be reinforced by FoMO, nomophobia and powerful emergent structural characteristics of SNS. Similarly to games, where the acquisition of artefacts or rewards reinforce the gamer into prolonging the gaming experience (Griffiths & Nuyens, 2017;King, Herd, & Delfabbro, 2018), SNSs exhibit a plethora of structural features that engage adolescents further in habitual behaviours (Griffiths, 2018;Turel & Osatuyi, 2018). SNS intensity and network size have been found as significant predictors of mobile SNS applications which are associated with smartphone addiction (Salehan & Negahban, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In future, a cohort study should be conducted to verify the causal association. 4 1,378(89.9) 1 Aggression score range : 27-135 2 Multiple answer available 3 High risk indicates 10 or higher scores in IGUESS 4…”
Section: E P U B a H E A D O F P R I N T Discussionmentioning
confidence: 99%
“…Yee (2006) reported that the factor driving the online role playing game (RPG) users towards gaming addiction was their immersion in the role they play in the game, through which they get a feeling of accomplishment when they win a match against someone else by creating increasingly stronger avatars throughout the game and feel satisfied with the social relationships formed in a virtual world [3]. Griffith et al (2017) defined the structural features of gaming addiction as sensory immersion, a feeling of accomplishment obtained from the game, and social interaction in a virtual world, and reported that the RPG genre had an association with gaming addiction [4].…”
Section: Introductionmentioning
confidence: 99%
“…The structural characteristics of the games (Griffiths and Nuyens 2017), as well as gamers' motivations such as coping with negative emotions, achievement (advancement and competition), socializing, and immersion (role-playing and escapism), are frequently cited as factors in the etiology of IGD (Kuss 2013). In addition, personality traits also appear to be important determinants in the enduring disposition of IGD and with controlling psychosocial, executive, and motivated behaviors (Kim et al 2016).…”
mentioning
confidence: 99%